2010
DOI: 10.1002/poc.1637
|View full text |Cite
|
Sign up to set email alerts
|

Redox properties and radical anions of fluorinated 2,1,3‐benzothia(selena)diazoles and related compounds

Abstract: In comparison with 2,1,3‐benzothia(selena)diazoles, electrochemical oxidation and reduction of their 4,5,6,7‐tetrafluoro derivatives and a number of related compounds were studied by cyclic voltammetry. For nine examples of this class, the first reduction peaks are reversible and corresponding radical anions (RAs) are long‐lived at 295 K in MeCN and especially in DMF. The oxidation peaks were irreversible and corresponding radical cations were not observed. Electrochemically generated RAs were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 69 publications
2
22
0
Order By: Relevance
“…5 and 6; the EPR spectrum of product of ECR of 3 in MeCN was reported earlier. 2 Experimental and DFT-calculated isotropic hyperfine coupling (hfc) constants are in reasonable agreement. The EPR spectrum of RA 3 for MeCN was reported earlier.…”
Section: Page 170mentioning
confidence: 82%
See 2 more Smart Citations
“…5 and 6; the EPR spectrum of product of ECR of 3 in MeCN was reported earlier. 2 Experimental and DFT-calculated isotropic hyperfine coupling (hfc) constants are in reasonable agreement. The EPR spectrum of RA 3 for MeCN was reported earlier.…”
Section: Page 170mentioning
confidence: 82%
“…Hydrogen replacement by fluorine affects many properties of (hetero) aromatics including (hetero) aromaticity itself. 28 Particularly, it enlarges EA1 of 2,1,3-benzothia/selenadiazoles, 2,3 i.e. their electron-acceptor ability, which can be used in the design of functional materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently DFT and MP2 calculations and cyclic voltammetry measurements showed that in 1,2,5‐thiadiazoles and their fused derivatives replacement of S by Se enlarges the positive electron affinity ( EA 1 ), which means that the Se compounds are stronger electron acceptors than their S congeners . This trend contradicts EA 1 and Allen electronegativity of S and Se, but can be tentatively explained by the better spin/charge delocalization in the more‐diffuse π MOs of the heavier chalcogen derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…According to the gas-phase (U)B3LYP/6-31+G(d) calculations, the first adiabatic electron affinity (EA) of compounds 5g and 5c are 1.55 and 1.93 eV, respectively, as compared with 0.22 eV for 1,2,5-selenadiazole and 1.06 eV for 2,1,3-benzoselenadiazole (10). [7] In the potential range 0 --2 V, the cyclic voltammogram (CV) of 5g contains three reduction peaks Ep Ep 1C = −1.40 V. [30] For both 5g and 5c the first reduction peak is H decoupling during acquisition. Spectra were acquired with recycle intervals of between 5 and 55 s, depending on the longitudinal relaxation time of the samples.…”
Section: Structure Elucidation By Xrd and 77 Se Nmrmentioning
confidence: 99%